Teachers as ‘Powerless Elites’: Emotions and Transformative Learning: A Refined Profession in an Era of Digitalisation and Artificial Intelligence (European Journal of Teaching and Education, 2024)
This research uses narrative analysis to examine the emotional experiences of five schoolteachers, teaching in five different schools in Hong Kong, Singapore, and Taiwan. The analysis shows the paradoxical perceptions about the (ir)replaceability of the teaching profession in the digital era. Findings include i. the strong mixed feelings experienced by teachers regarding the future of education that is embedded with digitalisation; ii. Meaning-making in teaching lies on the emotional engagement of teachers and quality teacher-student-relationship; iii. intense self-doubts on the roles of teachers in a virtual classroom were experienced in the beginning of the pandemic, but it has transformed into a refined roles upon critical self-reflection. This research investigates the emotionality of teachers in the virtual classroom, transformative learning has been the key to teachers’ refined roles despite society’s increasing reliance on artificial intelligence.